Scotland's mountain landscapes : a geomorphological perspective - Ballantyne, C. K. (Dunedin Academic Press, 2019)
The diversity of Scotland's mountains is remarkable, ranging from the isolated summits of the far northwest, through the tor-studded high plateau of the Cairngorms to the hills of the Southern Uplands. Colin Ballantyne explains the geological and geomorphological evolution of Scotland's mountains to form an unparalleled variety of mountain forms.